The use of soluble urokinase plasminogen activator receptor (suPAR) as a marker of sepsis in the emergency department setting. A current review. Issue 1 (2nd January 2021) - Velissaris, Dimitrios; Pierrakos, Charalampos; Karamouzos, Vasileios; Pantzaris, Nikolas Dimitrios; Gogos, Charalampos
ABSTRACT: Aim: The purpose of this review is to summarize all relevant publications regarding the use and validity of the soluble urokinase plasminogen activator receptor (suPAR) when used by clinicians in the emergency department (ED) for the detection and monitoring of patients with sepsis syndrome. Methods: A PubMed search was conducted in order to identify all publications related to the use of suPAR in sepsis patients in the ED setting. Results: Although suPAR is actively involved in the pathophysiology of sepsis, over the last 15 years, only a few studies have been published referring to its predictive validity in the ED. Conclusions: SuPAR can be easily and rapidly measured in an ED setting, and its role in the exclusion of an infection and the management of sepsis, alone or in combination to other biomarkers, should be further evaluated. The optimal cut-off value, the timing of the measurement and the role of the suPAR in an ED setting should be further investigated.